An Adaptive Mechatronic Exoskeleton for Force-Controlled Finger Rehabilitation - Dickmann , Thomas; Wilhelm, Nikolas J.; Glowalla , Claudio; Haddadin , Sami; van der Smagt , Patrick; Burgkart , Rainer (Frontiers in Robotics and AI, 2021)
This paper presents a novel mechatronic exoskeleton architecture for finger rehabilitation. The system consists of an underactuated kinematic structure that enables the exoskeleton to act as an adaptive finger stimulator. The exoskeleton has sensors for motion detection and control. The proposed architecture offers three main advantages. First, the exoskeleton enables accurate quantification of patient-specific rehabilitation progress. The configuration of the exoskeleton can be fully reconstructed using measurements from three angular position sensors placed on the kinematic structure. In addition, the actuation force acting on the exoskeleton is recorded. Thus, the range of motion (ROM) and the force and torque trajectories of each finger joint can be determined. Second, the adaptive kinematic structure allows the patient to easily perform various functional grasping tasks. The force control of the exoskeleton acts like a safeguard and limits the maximum possible joint torques during finger movement. Last, the system is compact, lightweight and does not require extensive peripherals. Therefore, it is easy to use in the home and can be operated in the absence of a physical therapist due to its safety features. Applicability was tested in three subjects.